Presenting characteristics, comorbidities, and outcomes of patients coinfected with COVID‐19 and Mycoplasma pneumoniae in the USA - Gayam, Vijay (J Med Virol, 2020)
Coronavirus disease 2019 (COVID‐19) caused by severe acute respiratory syndrome‐coronavirus 2 (SARS‐CoV‐2) is spreading at a rapid pace, and the World Health Organization declared it as pandemic on 11 March 2020. Mycoplasma pneumoniae is an "atypical" bacterial pathogen commonly known to cause respiratory illness in humans. The coinfection from SARS‐CoV‐2 and mycoplasma pneumonia is rarely reported in the literature to the best of our knowledge. We present a study in which 6 of 350 patients confirmed with COVID‐19 were also diagnosed with M. pneumoniae infection. In this study, we described the clinical characteristics of patients with coinfection. Common symptoms at the onset of illness included fever (six [100%] patients); five (83.3%) patients had a cough, shortness of breath, and fatigue. The other symptoms were myalgia (66.6%), gastrointestinal symptoms (33.3%‐50%), and altered mental status (16.7%). The laboratory parameters include lymphopenia, elevated erythrocyte sedimentation rate, C‐reactive protein, lactate dehydrogenase, interleukin‐6, serum ferritin, and D‐dimer in all six (100%) patients. The chest X‐ray at presentation showed bilateral infiltrates in all the patients (100%). We also described electrocardiogram findings, complications, and treatment during hospitalization in detail. One patient died during the hospital course.